Pengaruh Leverage, Arus Kas Bebas, dan Efisiensi Operasional terhadap Nilai Perusahaan Makanan dan Minuman - Muhammad Ihsan; Gatot Nazir Ahmad; Andy Andy (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of leverage (DER), free cash flow (FCF), and operational efficiency using inventory turnover (ITO), and receivables turnover (RTO) on company value, with company size as a control variable, in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018–2023 period. The method used is panel data regression with the Fixed Effect Model approach. The results of the study show that leverage has a significant negative effect, and inventory turnover has a significant positive effect on the company's value. Meanwhile, FCF and RTO had no significant effect, while company size had a negative effect. Robustness checks with PBV as proxy for alternative values showed relatively consistent results. These findings support the signal theory, that operational efficiency and a well-managed financial structure can strengthen investors' perception of a company's value.